ANALISIS PENERAPAN GREEN BUSINESS TERHADAP KINERJA UKM DI KOTA TARAKAN - Mohamad Nur Utomo; Sulistya Rini Pratiwi (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2021)
Isu green business is a small part of a large real issue has hit the headlines of economic growth in the future, namely the sustainability of the business. The SME sector has an important role to make it happen. This role is obtained for the SME sector is a sector which has the closest relationship with the community. The purpose of research is to know the extent to which the implementation of green business has made SMEs in the town of Tarakan and know the role that implement green business input green, green process, green output, green marketing, government regulation and public awareness affect the performance of SMEs in the city of Tarakan. The results showed that the perpetrators of Small and Medium Enterprises in the town of Tarakan is said to have implemented environmentally friendly businesses. And the amount of Financial Performance for Small and Medium positively and significantly influenced by Green Output, Green Marketing, and Public Awareness Levels. As for Green Input, Green Process and Government Regulation, a negative effect but not significant.